"SEHATI LESTARI": STRENGTHENING HEALTH CADRES TO REALIZE A TB-FREE AND HEALTHY COMMUNITY: "SEHATI LESTARI": PENGUATAN KADER KESEHATAN WUJUDKAN MASYARAKAT BEBAS TBC DAN HIDUP SEHAT - Prodyanatasari, Arshy; Pratiwi, Wahyu Nur; Astutik, Wahyu Sri; Laksono, Adi; Werdiningsih, Wiwik; Anikasari, Erni; Fernanda, jerhi Wahyu (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: The low level of public understanding about tuberculosis (21.9%) and the limited implementation of home ventilation as a preventive measure (31.3%) prompted the launch of the “SEHATI LESTARI” program, which focuses on strengthening health cadres to create a tuberculosis-free community. Objective: This activity aimed to increase community knowledge about TB prevention, promote the adoption of healthy behaviors, and empower health cadres as agents of change at the community level. Method: The program, conducted from 16 September to 15 October 2024 with 32 participants in Tunge Village, combined interactive lectures, simulations, and field audits to ensure a comprehensive understanding. Results: Post-activity evaluations demonstrated significant improvements: participants’ knowledge of TB increased from 21.9% to 71.9%, the adoption of home ventilation practices rose from 31.3% to 68.8%, and 32 trained health cadres were successfully established. Conclusion: This community-based empowerment program through health cadres proved effective in improving knowledge and behavior related to TB prevention. To ensure program sustainability, it is recommended to establish a monthly cadre forum facilitated by the community health center (Puskesmas), integrate the TB education module into routine Posyandu activities, and develop adaptable intervention designs for other agricultural areas with similar characteristics.